2020
DOI: 10.21597/jist.643987
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Neurotoxic and Immunotoxic Effects of the Chinar (Platanus orientalis L.) Tree Leaf Infusion Against Ethanol Toxicity in Rats

Abstract: In this study, immunotoxic and neurotoxic effects of leaf infusion of Platanus orientalis L. (PO) were investigated in rats ethanol-induced toxicity. Neurotoxic effects of ethanol were evaluated by measuring acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) in rat brain tissue. Immunotoxic effects were evaluated by adenosine deaminase (ADA) and myeloperoxidase (MPO) biomarkers in rat liver, lung, erythrocyte and spleen tissues. Thirty male Wistar rats were divided into five groups after toxicity stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Medicinal plants and their bioactive compounds are used against immunotoxic and neurotoxic damage caused by chemicals, pesticides and heavy metals (Dogan et al, 2020). Ozok and Celik (2019), in their study to determine the immunotoxic effects of Tiliaplatyphyllos Scop plant infusion of ethanol in rats, stated that ADA activity in liver tissue decreased significantly, and the plant extract had a positive effect on enzyme activity with its antioxidant effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicinal plants and their bioactive compounds are used against immunotoxic and neurotoxic damage caused by chemicals, pesticides and heavy metals (Dogan et al, 2020). Ozok and Celik (2019), in their study to determine the immunotoxic effects of Tiliaplatyphyllos Scop plant infusion of ethanol in rats, stated that ADA activity in liver tissue decreased significantly, and the plant extract had a positive effect on enzyme activity with its antioxidant effect.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that there are two types of cholinesterase in the body, AChE and BChE (Gulcin et al, 2016;Turkan 2021).Similarly, adenosineaminase and myeloperoxidase are biomarkers of the immune system in vertebrates. While ADA is an enzyme that catabolizes adenosine or deoxyadenosine, MPO is an enzyme that catalyzes the formation of hypochlorous acid or hypothiocyanide (Tamura et al, 2016;Lu et al, 2018;Dogan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%